Rethinking Criminal Justice in Maine: An Interview with Commissioner Joseph Lehman - Lehman, Joseph (Maine Policy Review, 1996)
Relative to other states, Maine enjoys low crime rates. Yet crime, and the fear of random, violent crimes are of concern for many Mainers. In this interview, Maine Department of Corrections Commissioner Joseph Lehman addresses these concerns and articulates a new vision for Maine’s criminal justice system based on prevention and the principles of restorative justice.